2017
DOI: 10.1016/j.ssc.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of local and nonlocal hybridization on formation and condensation of excitons in the extended Falicov-Kimball model

Abstract: We study the combined effects of local and nonlocal hybridization on the formation and condensation of the excitonic bound states in the extended FalicovKimball model by the density-matrix-renormalization-group (DMRG) method. Analysing the resultant behaviours of the excitonic momentum distribution N (q) we found, that unlike the local hybridization V , which supports the formation of the q = 0 momentum condensate, the nonlocal hybridization V n supports the formation of the q = π momentum condensate. The comb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The first one strongly supports the formation of condensate, while the second one destroys it completely. In systems with equal parity orbitals, the local and nonlocal hybridization can coexist and for this case we have found [22] that the combined effect of both hybridizations strongly support the formation of zero-momentum condensate the existence of which can yield the reasonable explanation for the pressure-induced resistivity anomaly observed experimentally in T mSe 0.45 T e 0.55 compound [23].…”
Section: Introductionsupporting
confidence: 60%
“…The first one strongly supports the formation of condensate, while the second one destroys it completely. In systems with equal parity orbitals, the local and nonlocal hybridization can coexist and for this case we have found [22] that the combined effect of both hybridizations strongly support the formation of zero-momentum condensate the existence of which can yield the reasonable explanation for the pressure-induced resistivity anomaly observed experimentally in T mSe 0.45 T e 0.55 compound [23].…”
Section: Introductionsupporting
confidence: 60%
“…In this article we focus our attention on the properties of the EI phase induced by local hybridization V in the one dimension. Although it is generally known that there is no nonvanishing P d f = d + f expectation value in the limit of vanishing hybridization (no spontaneous hybridization), the studies that we performed in the past years on various extensions of the original Falicov-Kimball model showed that it is possible to dramatically enhance excitonic correlations in the limit of small, but finite V by additional interactions/factors [36][37][38][39]. The effects of most important interactions are discussed in this review.…”
Section: Introductionmentioning
confidence: 86%
“…In this situation, the most promising candidates for studying this phenomenon seem to be the systems with equal parity of d and f orbitals, where the nonlocal hybridization H n can be written as [38]:…”
Section: Combined Effects Of Local and Non-local Hybridization With Ementioning
confidence: 99%
See 2 more Smart Citations